Characteristics of the strain glass transition in as-quenched and 250 °C early-aged Ti48.7Ni51.3 shape memory alloy. (November 2016) - Chien, Chen; Tsao, Cheng-Si; Wu, Shyi-Kaan; Chang, Chun-Yu; Chang, Pei-Chi; Kuo, Yung-Kang
Abstract: Characteristics of the strain glass transition exhibited in as-quenched and 250 °C 1–5 h aged Ti48.7 Ni51.3 SMA were studied by various tests/measurements. The results of frequency-dependent storage modulus vs. temperature measurement, the temperature-dependent resistivity, thermal conductivity, and specific heat tests demonstrated the signature and characteristics of the strain glass transition exhibited in as-quenched and 250 °C early-aged Ti48.7 Ni51.3 SMA. The plate-/disk-like morphology and spatially heterogeneous distribution of the real Ni-rich nanodomains in as-quenched and 250 °C 1–5 h aged specimens were quantitatively characterized using small-angle X-ray scattering (SAXS) technique. The formative origin of the real nanodomains and the relationship between the real nanodomains and the strain nanodomains are proposed accordingly. Experimental results indicated R-like phase and Ti3 Ni4 -like precipitates co-existing in the strain glass of 250 °C early-aged specimens, and they also demonstrated the growth behavior of the real nanodomains exhibited in specimens during thermal aging. It was also found that increasing the aging time can elevate the T g from ∼−60 °C to ∼−20 °C, which indicates the tunable characteristic of T g for as-quenched Ti48.7 Ni51.3 SMA. Graphical abstract: Highlights: Strain glass characteristics in Ti48.7 Ni51.3 SMA were studied by various methods. 2D SAXS patterns provide direct evidence of plate-/disk-like shape nanodomains. These strain glass nanodomains are nucleated heterogeneously in different grains. 1D SAXS profiles quantitatively determine the nanodomains' radii and thicknesses.